Performance of groundcover on surface temperature reduction in the application of the extensive green roof - Lim, Sun Tjet; Shahidan, Mohd Fairuz; Abdul Rahman, Asraf (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
Malaysia’s climate is struggling with unusually hot and dry weather from February to May 2016. Temperatures soared to the limits of a new record. One of the solutions is by having green roof to reduce the heat transfer in urban microclimate and buildings. Thus, the evaluation of potential plants in this study is to understand their performance in surface temperature reduction. In this study, the field measurements was carried out with ten types of groundcover and one exposed soil and one selected concrete flooring on three clear days. The measurement is taken from 8 AM to 6 PM and recorded at one-hour interval using an infrared thermometer. This study was done to compare the surface temperature of green roof and exposed bare roof within the same outdoor ambient environment. The result from this study indicates that Eremochloa ophiuroides and Rhoeo spathacea are suitable for planting in extensive rooftop system. Eremochloa ophiuroides and Rhoeo spathacea significantly provide the value of the average percentage of surface temperature reduction which was 18.9% and 18.8% respectively. Thus, it is recommended that both species are suitable for extensive roof planting. This knowledge can be applied by professionals in landscape architecture, horticulture, urban planning and design to provide better rooftop planting material in tropical urban environments.